William Whyte's The Organization Man: A flawed central concept but a prescient narrative - Dallas Hanson; Wayne O'Donohue (Management Revue, 2010)
William H Whyte's concept of organization man is now used in bowdlerised form, shorn of its polemical core. It was an appeal against the situation of people in the big organiations taking shape after World War Two, belonging to the organization rather than simply working for it, earning rewards that are also, in the end, traps. In the current worlds of agile organizations with serially loyal staff these people no longer exist, and in fact the only group that fits the Whyte pattern are dedicated priests. At the same time, the polemic is never more relevant than today because we live in a world in which we are closely surveilled on many levels using ever more sophisticated technology, and in which many human resource management practices increase the power of organization over individual. William Whyte's time has come.
Keywords: 650; Whyte; priest; collectivism; organization; organizationality